Post-harvest operations and aflatoxin levels in rice (Oryza sativa). (December 2015) - Prietto, Luciana; Moraes, Paola Silveira; Kraus, Rosana Basso; Meneghetti, Volnei; Fagundes, Carlos Alberto Alves; Furlong, Eliana Badiale
Abstract: This study evaluated the effect of post-harvest operations on the occurrence of aflatoxins in rice ( Oryza sativa ) samples. Newly harvested rice was subjected to stationary, intermittent, or combined drying, and stored in concrete storehouses during 10 months. The aflatoxins were extracted with methanol: potassium chloride and quantified by HPLC-FL. After ten months of storage, the highest aflatoxin levels were found in rice bran, of which the values were above 25 μg/kg for the sum of the aflatoxins (B1 + B2 + G1 + G2 ). The rice fractions of the endosperm and husk from the intermittent drying showed the lowest aflatoxin levels during the storage. Highlights: Stationary drying resulted in higher aflatoxin contamination. Bran showed higher aflatoxin contamination. Intermittent drying is recommended, due to less contamination with aflatoxins.